Projecting our past to the future - Challenges and results: The case of asinou church - Papaefthymiou, M.; Nikolakopoulou, Vasiliki; Leventis, Georgios; Domajnko, Dora; Ioannides, Marinos; Papagiannakis, George; Moura Santo, P. (My University, 2017)
Eurographics Workshop on Graphics and Cultural Heritage. All rights reserved. In this paper, we present some of the novel results of the Marie Curie Initial Training Network for Digital Cultural Heritage (ITN-DCH) project, describing briefly the work done focusing on the project's first case study: the Panagia Phorviotisa of Asinou, an UNESCO World Heritage Listed (WHL) monument in Cyprus. The paper introduces some challenges and the importance of multidisciplinary, sustainable research and development in the emerging domain of DCH in Europe. The different methodologies address these challenges through a professional network of partners including Academia, Research and Industry. The paper describes the 3D documentation of the church and how the data acquired can be used and re-used in Mixed Reality (MR) applications using also Deep Learning techniques, as well as in Education.
Keywords: 3-D documentation; Digital cultural heritages; Emerging domains; Future challenges; Learning techniques; Research and development; UNESCO world heritages; Mixed reality